Efektivitas Pembelajaran Bahasa Arab Menggunakan Modul Berbasis Higher Order Thinking Skills (HOTS) - Ridho, Yusuf; Wasilah; Nazarmanto (Institut Muslim Cendekia, 2025)
This study aims to evaluate the effectiveness of Arabic language learning using modules based on Higher Order Thinking Skills (HOTS) in enhancing the higher-order thinking abilities of fifth-grade students at MIN 2 Palembang. Employing a mixed-methods approach with a sequential explanatory design, the research began with the collection and analysis of quantitative data through pre-tests and post-tests, followed by qualitative data obtained from interviews, observations, and documentation. The findings indicate that prior to the implementation of the HOTS-based module, learning was still conventional and teacher-centered, which limited the development of students' critical and creative thinking skills. After the module was implemented, there was a notable increase in the average learning outcomes, from 74.83 to 80.17. Furthermore, interviews with teachers and students confirmed that this approach was more engaging, challenging, and encouraged active cognitive involvement. Therefore, Arabic language learning based on HOTS has proven effective in improving both student achievement and higher-order thinking skills. This research contributes to the development of innovative teaching strategies in madrasahs, particularly in strengthening higher-order thinking literacy within Arabic language education.